Artificial Intelligence in Marketing Communication: A Comprehensive Exploration of the Integration and Impact of AI - Durmus Senyapar, Hafize Nurgul (Technium Social Sciences Journal, 2024)
This study investigates the transformative impact of artificial intelligence (AI) on marketing communications through an evaluation research approach. Focused on enhancing personalization, efficiency, and strategic insight, the study explores AI’s applications in content creation, customer service, social media, influencer marketing, and predictive analytics. The results reveal a paradigm transition in customer engagement and behaviour analysis, highlighting AI’s role in providing profound insights and facilitating real-time interactions. Personalized marketing and targeted advertising have evolved, with AI analysing vast datasets to craft tailored messages, significantly enhancing communication relevance. AI’s impact extends to content creation and curation, accelerating processes through natural language generation and improving content personalization. Moreover, AI-driven chatbots redefine customer service, providing 24/7 personalized support and actively contributing to marketing strategies. Social media and influencer marketing benefit from AI’s optimization of content delivery, personalization, and campaign impact measurement. The synergy between AI and predictive analytics anticipates consumer behavior, enabling precise targeting and optimizing the customer journey. The study concludes with implications for businesses, advocating strategic AI integration for sustained growth, and emphasizes the necessity of staying attuned to emerging AI innovations in future research. This research serves as a roadmap, guiding businesses toward successfully navigating the digital era’s evolving marketing communications view.